Unpacking the Political Economy of Member States’ Withdrawal from ECOWAS: The Cases of Burkina Faso, Mali, and the Niger Republic - Celestina Ekene Chukwudi; Nick Peter Essien; Paul Chibuike Ezebuilo (PERSPEKTIF, 2025)
The Economic Community of West African States (ECOWAS) is a regional organisation that has worked since its inception to maintain member states' unification and improved relationships with other regional and Western nations to ensure political and socio-economic development. Despite all efforts, ECOWAS faces numerous challenges, such as an undemocratic government, insecurity, a lack of member cooperation, and, most recently, the exit of its trio-member nations. The study explores the political and socio-economic consequences of ECOWAS member nations like Mali, Burkina Faso, and the Niger’s exit, and the effect on regional integration and cooperation. Rational Choice theory was adopted as a theoretical framework suitable for the underpinnings of this study. A qualitative research method, i.e., content analysis, was adopted to analyse the collated data. The study used secondary sources of data collection, e.g., textbooks, journals, conference proceedings, and internet sources, which were thematically discussed. The study finds that the trio-member nations that withdrew their membership are not parasitic and dependent on ECOWAS but have contributed to the continuous well-being of the organisation towards promoting and ensuring the regional integration, cooperation, growth, and development at large. The study concluded that the ECOWAS political and socio-economic system has been seriously affected, including the organisational image and recognition in Africa and globally. The study recommends that policymakers and international organisations such as ECOWAS, AU, EU, etc., should ensure inclusivity of all member nations, which would bring a sense of value and belonging that will keep them committed and loyal to their organizations, to avoid any member nation rising to disobey the principles of this organisation with the mindset of exit.